POTENTIAL ALPHA GLUCOSIDASE INHIBITOR FROM SELECTED ZINGIBERACEAE FAMILY - Hasimun, Patonah; Adnyana, I Ketut; Valentina, Rizka; Lisnasari, Euis (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study aimed to evaluate Zingiberaceae family as potential sources of alpha-glucosidase inhibitors (AGIs). Methods: A 16 species of selected Zingiberaceae family were macerated by ethanol 96%. The extracts were filtered and concentrated by rotary evaporator. Phytochemical analysis carried out on the dry extract. AGI was assayed in 50 mM phosphate buffer at pH 6.8 with 5 mM p-nitrophenyl-αD-glucopyranoside as the substrate. Alpha-glucosidase activity was determined by measuring the release of the yellow p-nitrophenol at 400 nm using a spectrophotometer UV-Vis, and the percentage of inhibition was calculated. Results and Conclusion: The Zingiberaceae family showed IC against alpha-glucosidase varies range from 28.4 µg/ml to 269.2 µg/ml. Curcuma longa L., Zingiber cassumunar Roxb., Curcuma heyneana Val. Et van zijp, Curcuma xanthorrhiza Roxb., Zingiber ottensii Val., showed the highest inhibition against alpha-glucosidase, with IC 50 50 28.4, 49.0, 78.2, 78.9, and 79.0 µg/ml, respectively. The Zingiberaceae family is potential sources as an alternative medicine to treated diabetes mellitus. Keywords: Zingiberaceae, Alpha-glucosidase inhibitor, Diabetes mellitus, Phytochemistry content.